The Problem of Incongruities in Understandings of the Spirit of UN Institutional Efforts in the Field of Maintaining and Restoring International Peace and Security - S. V. Korostelev (Управленческое консультирование, 2022)
This article is devoted to the problem of the political and legal substantiation of the actions of state authorities to determine and declare the need for various forms of “peace operations” in the framework of the common interests of the international community and the common goals of international and collective security systems for other participants in international communication.Aim. Eliminate methodological problems in defining the content of terms “peacebuilding”, “peacekeeping (peace enforcement)” while institutionalizing the use of force within the framework of universal and regional agreements in the field of security.tasks. Formulate the lines of reasoning for the actions of state authorities in the field of political and legal substantiation of the use of national armed formations outside the national territory to solve the problems of maintaining and restoring international peace and security.Methodology. In the course of the study, the author turned to resolutions and transcriptsof meetings and other documents of the Security Council and the UN General Assembly, international normative legal acts, model acts of the Parliamentary Assembly of the Collective Security Treaty Organization and the Interparliamentary Assembly of CIS member states. To draw conclusions, a search for facts and objective connections between them was carried out to confirm that the modern practice of states is carried out in accordance with the ideals underlying the modern system of ensuring international security, built around the UN paradigm, which in turn is aimed at protecting human dignity and deliverance from the scourge of war.results. The use of armed force is often a necessary condition both for maintaining peace and for preventing the outbreak, escalation, continuation and renewal of conflicts. Preservation of peace in a broad sense should be interpreted as a goal and as a process of forming a common vision of the international community based on the needs of all actors. However, many problems of political mobilization of both national and international communities are generated by incongruities in understanding the content of a number of basic concepts that shape the interaction of states and circulate in public discourse. That is, the improvement of the “language” in which the main international actors conduct discourse in the field of ensuring international security is an objective necessity for the development of a modern theoretical and methodological base for the process of legitimization of political decisions by government authorities.Conclusions. To ensure the coordination of the wills of the participants in international communication, decisions of state authorities to take action on the use of force outside the national territory to protect common interests should be based on a unified interpretation of the content of the concepts of “peacebuilding”, “peacekeeping (peace enforcement)” as a “fair use of force” in order to be uniformly acceptable for various political regimes and correspond to the national-cultural, religious and other traditions of different peoples.